PENERAPAN METODE PROBLEM SOLVING DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MATA KULIAH ALJABAR DAN TRIGONOMETRI - Imelda Imelda (Universitas Islam Sumatera Utara, 2018)
Abstract. This study is a classroom action research. The purpose of this research is (1) to describe the application of problem solving method in improving mathematics problem solving students of mathematics education program of Catholic University of Santo Thomas North Sumatera and (2) to describe the improvement of mathematics problem solving ability of mathematics education student in Algebra and Trigonometry. The result of this research shows that the result of problem solving test of mathematics cycle I is students who do not have problem solving ability as much as 3 people (30%), while students have math problem solving ability as much as 7 people (70%) and percentage of observation sheet lecturer activity amounted to 70.90%. Based on the result of math problem solving test in cycle 2, there were 1 (10%) students who did not have the ability to solve mathematics problem, while the students who have problem solving ability 9 students (90%) and lecturer activity percentage of 85.50% experienced an increase from cycle I of 6.5%. Based on the results of this acquisition then the group (classical) can be said that students have the ability to solve problems in Algebra and Trigonometry courses and increase problem-solving abilities by 20%. Keywords: problem solving method and problem solving ability.